A Review of Infrared Thermography Applications for Civil Infrastructure - Shrestha, Prabal; Rifai, Sahabeddin; Abla, Feras; Barth, Karl; Avci, Onur; Seek, Michael; Halabe, Udaya (Structural durability & health monitoring, 2025)
Civil infrastructure is continuously subject to aging and deterioration due to multiple factors, which lead to a decline in performance and impact structural health. Accumulated damage on structures increases operational costs and poses significant risks to public safety. Effective maintenance, repair, and rehabilitation strategies are needed to ensure civil infrastructure’s overall safety and reliability. Non-Destructive Evaluation (NDE) methods are utilized to assess latent damage and provide decision-makers with real-time information for mitigating hazards. Within the last decade, there has been a significant increase in the research and development of innovative NDE techniques to improve data processing and promote efficient and accurate infrastructure assessment. This paper aims to review one of those methods, namely, Infrared Thermography (IRT), and its applications in civil infrastructure. A comprehensive review is presented by investigating numerous journal articles, research papers, and technical reports describing numerous IRT applications for bridges, buildings, and general civil structures made from different materials. The capability of IRT to identify and pinpoint anomalies, typically in the early stages of degradation, has excellent potential to improve the safety and shore up the dependability of civil infrastructures while reducing expenses tied to maintenance and rehabilitation. Furthermore, the non-invasive nature of IRT is beneficial in mitigating disturbances and downtime that may occur during various inspection procedures. It is highlighted that IRT is a highly versatile and effective tool for infrastructure condition assessment. With further advancement and fine-tuning of the available techniques, it is likely that IRT will continue to gain significant popularity in maintaining and monitoring civil infrastructure.